Galleria mellonella Infection Model Identifies Both High and Low Lethality of Clostridium perfringens Toxigenic Strains and Their Response to Antimicrobials - Kay, Sammy; Edwards, Joseph; Brown, Joseph; Dixon, Ronald (Frontiers in Microbiology, 2019)
Research progress into mechanisms of the anaerobe Clostridium perfringens associated diseases has been frustrated by the lack of reliable infection models. Wax moth larvae (Galleria mellonella) have emerged as a viable alternative to other models of infection since they are economic, survive at 37°C and require no specialist equipment. This study aims to establish to what extent G. mellonella larvae can be used to study the virulence of C.perfringens strains and its suitability for studying novel treatment strategies by an improved time-lapse approach to data collection. Mortality and morbidity rates of larvae challenged with 105 CFU of C. perfringens isolates from various sources were observed over 72h and dose response data obtained. Phenoloxidase enzyme activity was investigated as a marker for immune response and tissue burden assessed by histopathological techniques. Results demonstrate that C. perfringens is pathogenic towards G. mellonella although potency varies dramatically between C.perfringens isolates and the reference strain ATCC 13124 was shown to be avirulent. Infection with C.perfringens strains activated the melanisation pathway resulting in melanin deposition but no increase in enzyme activity was observed. Efficacy of antibiotic therapy (penicillin G, bacitracin, neomycin and tetracycline) administered parenterally to some extent correlates with that of in vitro analysis. The findings suggest G. mellonella might be a useful in vivo model of infection and convenient as a pre-screening assay for virulence of C.perfringens strains or as a simple, cheap and rapid in vivo assay in the first stage development of novel therapeutics against anaerobes.